Skeletal muscle ex vivo mitochondrial respiration parallels decline in vivo oxidative capacity, cardiorespiratory fitness, and muscle strength: The Baltimore Longitudinal Study of Aging - Gonzalez‐Freire, Marta; Scalzo, Paul; D'Agostino, Jarod; Moore, Zenobia A.; Diaz‐Ruiz, Alberto; Fabbri, Elisa; Zane, Ariel; Chen, Brian; Becker, Kevin G.; Lehrmann, Elin; Zukley, Linda; Chia, Chee W.; et al. (Aging cell, 2018)
Summary Mitochondrial function in human skeletal muscle declines with age. Most evidence for this decline comes from studies that assessed mitochondrial function indirectly, and the impact of such deterioration with respect to physical function has not been clearly delineated. We hypothesized that mitochondrial respiration in permeabilized human muscle fibers declines with age and correlates with phosphocreatine postexercise recovery rate (kPCr), muscle performance, and aerobic fitness. Mitochondrial respiration was assessed by high‐resolution respirometry in saponin‐permeabilized fibers from vastus lateralis muscle biopsies of 38 participants from the Baltimore Longitudinal Study of Aging (BLSA; 21 men, age 24–91 years) who also had available measures of peak oxygen consumption (VO2max) from treadmill tests, gait speed in different tasks, 31P magnetic resonance spectroscopy, isokinetic knee extension, and grip strength. Results indicated a significant reduction in mitochondrial respiration with age (p < .05) that was independent of other potential confounders. Mitochondrial respiratory capacity was also associated with VO2max, muscle strength, kPCr, and time to complete a 400‐m walk (p < .05). A negative trend toward significance (p = .074) was observed between mitochondrial respiration and BMI. Finally, transcriptional profiling revealed a reduced mRNA expression of mitochondrial gene networks with aging (p < .05). Overall, our findings reinforce the notion that mitochondrial function declines with age and may contribute to age‐associated loss of muscle performance and cardiorespiratory fitness.